A low-moisture lithium battery separator and preparation method thereof

By coating the lithium battery separator with polystyrene-Al2O3 composite material, the problems of high moisture content, poor heat resistance and insufficient mechanical properties of the separator are solved, and a separator with low moisture, high heat resistance and high mechanical strength is realized, improving improve battery safety and performance.

CN117219966BActive Publication Date: 2025-01-24JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311292081.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-01-24
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The existing lithium battery separators have problems such as high moisture content, poor heat resistance and insufficient mechanical performance, resulting in deterioration of battery performance and safety hazards.

Method used

Polystyrene-Al2O3 composite material is used as the coating layer, and the composite material is coated on both sides of the polyolefin separator to prepare a low-moisture lithium battery separator. The composite material is composed of polystyrene, Al2O3, hydrolyzed polymaleic anhydride dispersant, sodium hydroxymethylcellulose thickener, COPNA resin binder and silanol nonionic surfactant.

Benefits of technology

The moisture content of the separator is significantly reduced, its heat resistance and mechanical strength are improved, the energy consumption of subsequent drying and baking is reduced, and the safety and performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004481773220000071
    Figure BDA0004481773220000071
Patent Text Reader

Abstract

The present invention relates to the technical field of battery separators, specifically to a low-moisture lithium battery separator and a preparation method thereof. A polystyrene-Al2O3 composite material is prepared using aluminum oxide and polystyrene, and then a coating slurry is prepared using the composite material with a hydrolyzed polymaleic anhydride dispersant and a sodium hydroxymethylcellulose thickener, and an adhesive and a silanol nonionic surfactant are added as a wetting agent, and then the slurry is coated on a polyolefin separator to prepare a composite separator. In the present invention, polystyrene has strong hydrophobicity and extremely low water absorption. By modifying aluminum oxide with polystyrene, the problem of high moisture content caused by water absorption of the coated separator can be significantly improved. At the same time, aluminum oxide has good high temperature resistance and thermal conductivity, which is beneficial to improving the heat resistance of the coating, thereby improving the heat resistance of the separator. The prepared composite separator has excellent heat resistance, and has low moisture content and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a low-moisture lithium battery separator and a preparation method thereof. Background Art

[0002] As a new type of secondary battery, lithium battery has the advantages of high energy density and long cycle life. Its application scope is constantly expanding and is widely used in portable electronic devices, energy storage and power vehicles. With the rapid development of the new energy industry, lithium batteries are increasingly used in power vehicles. As an important component of lithium batteries, the diaphragm can effectively prevent the positive and negative electrodes from short-circuiting. Therefore, the diaphragm has a very important impact on the safety of lithium batteries. Therefore, the market has higher requirements for the performance of the diaphragm.

[0003] Polyolefin separators are currently the most widely used lithium battery separators. However, the existing polyolefin separators on the market also have some disadvantages: ① It is easy to absorb water in the environment or the moisture introduced during the coating process is not easy to dry, and the moisture introduced by the separator into the battery will react with the lithium salt in the electrolyte to generate HF, which will destroy the SEI film and cause secondary film formation, resulting in deterioration of battery performance; ② The low ionic conductivity makes the internal resistance of the battery large, which is not conducive to the charging and discharging of lithium-ion batteries at high rates; ③ The mechanical strength is low and the puncture resistance is poor. It is easy to be punctured, causing the positive and negative electrodes of the battery to short-circuit and form thermal runaway; ④ The melting point of polyolefin materials is very low. When the battery has thermal runaway, the separator is prone to rupture, resulting in more serious thermal runaway, which can cause the battery to burn or even explode. To address the problems of low ionic conductivity and poor mechanical properties of polyolefin diaphragms, the main solution currently is to coat one or both sides of the polyolefin diaphragm with a ceramic coating; to address the problem of poor heat resistance of polyolefin diaphragms, by coating the surface of the polyolefin diaphragm with a high-temperature resistant ceramic coating, the closure of the diaphragm can be delayed to 150°C, but the closure temperature of 150°C cannot completely prevent lithium batteries from short-circuiting at high temperatures and the resulting spontaneous combustion. Therefore, it is necessary to further improve the heat resistance of the diaphragm and reduce the risk of diaphragm rupture to improve the safety of the battery; and to address the problem of high moisture content in polyolefin diaphragms, the main solution currently is to place the diaphragm in a drying room to dry and remove water and to bake the battery to remove water. This type of solution requires a lot of manpower, material resources and energy consumption, which greatly reduces the profit margins of diaphragms and batteries.

[0004] In order to solve the above problems and improve the heat resistance and mechanical strength of the battery separator, the present invention provides a low-moisture lithium battery separator and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a low-moisture lithium battery separator and a preparation method thereof to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A low-moisture lithium battery separator, comprising a base film and a coating layer, wherein the coating layer is arranged on both sides of the base film; the coating layer comprises the following components: a polystyrene-Al2O3 composite material, a dispersant, a thickener, a binder, a wetting agent, and ultrapure water.

[0008] More optimally, the dispersant is hydrolyzed polymaleic anhydride, the thickener is sodium hydroxymethyl cellulose, the adhesive is COPNA resin, and the wetting agent is a silanol nonionic surfactant.

[0009] More optimally, the coating layer includes the following components, calculated by mass percentage: 0.2%-0.7% dispersant, 15%-35% polystyrene-Al2O3 composite material, 0.15%-0.85% thickener, 1%-11% binder, 0.1%-0.7% wetting agent, and the balance is ultrapure water.

[0010] More optimally, the base membrane is a polyolefin membrane.

[0011] A method for preparing a low-moisture lithium battery separator, the method for preparing the battery separator comprising the following steps:

[0012] Step 1: Take a dispersant and a polystyrene-Al2O3 composite material, add them to ultrapure water, mix them evenly, add a thickener, a binder, and a wetting agent, stir, and filter to obtain a polystyrene-Al2O3 composite material coating slurry;

[0013] Step 2: Apply the polystyrene-Al2O3 composite material coating slurry on both sides of the polyolefin separator, bake and roll it up to obtain a low-moisture lithium battery separator.

[0014] More optimally, the preparation method of the polystyrene-Al2O3 composite material is: adding a polystyrene solution to an Al2O3 dispersion, stirring evenly to obtain a mixed solution, centrifuging, washing, and vacuum drying to obtain a polystyrene-Al2O3 composite material.

[0015] More optimally, the preparation method of the polystyrene solution is: adding polystyrene to acetone, mixing evenly, heating to 42-45° C., stirring at a rotation speed of 350-400 rpm for 8-9 hours to obtain a polystyrene solution.

[0016] More optimally, the preparation method of the Al2O3 dispersion is: take Al2O3 powder and ultrapure water, stir for 90-100 minutes, and then ultrasonically disperse for 8-9 hours to obtain the Al2O3 dispersion.

[0017] More optimally, the polystyrene solution is added to the Al2O3 dispersion, stirred at a speed of 400-500 rpm for 2-3 hours, and then treated at 45KHZ and 450-500w ultrasonic power for 5-6 hours to obtain a mixed solution.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] (1) The present invention uses aluminum oxide and polystyrene to prepare a polystyrene-Al2O3 composite material, and then uses the polystyrene-Al2O3 composite material, hydrolyzed polymaleic anhydride dispersant, sodium hydroxymethylcellulose thickener, and adds COPNA resin as an adhesive and a silanol nonionic surfactant as a wetting agent to prepare a polystyrene-Al2O3 composite material coating slurry, and then coats the polystyrene-Al2O3 composite material coating slurry on a polyolefin diaphragm to prepare a polystyrene-Al2O3 composite material modified composite diaphragm. The polystyrene-Al2O3 composite material modified composite diaphragm prepared by the method provided by the present invention is added with a polystyrene-Al2O3 composite material. Among them, polystyrene has strong hydrophobicity and extremely low water absorption. Through the modification of aluminum oxide by polystyrene, the problem of high moisture content caused by water absorption of Al2O3 coated diaphragm can be significantly improved, thereby greatly reducing the subsequent investment in manpower, material resources and energy consumption, and thus greatly improving the profit margin of diaphragm and battery.

[0020] Secondly, the composite diaphragm modified with the PS-Al2O3 composite material provided by the present invention, wherein aluminum oxide has good high temperature resistance and thermal conductivity, is beneficial to improving the heat resistance of the coating, thereby improving the heat resistance of the composite diaphragm.

[0021] In view of the technical defects of the prior art such as high moisture content, poor heat resistance and mechanical properties of the diaphragm, the present invention provides a lithium-ion battery diaphragm with low moisture content, high heat resistance and high mechanical properties. The prepared composite diaphragm has excellent heat resistance, low moisture content and high mechanical strength. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The purchasers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include:

[0024] The Al2O3 powder used in the present invention has a D50 of 0.7-1.0 μm; polystyrene: can be purchased from Kunshan Jinkaiwo Plastic Co., Ltd., item number: 825; the dispersant is hydrolyzed polymaleic anhydride, which can be purchased from Zhengzhou Alpha Chemical Co., Ltd.; the adhesive is COPNA resin, which can be purchased from Wuhan Baohua Petrochemical New Materials Development Co., Ltd., model: FJSZ; the wetting agent is a silanol non-ionic surfactant, which can be purchased from Dongguan Gaussjin Fine Chemical Co., Ltd., model: GSK-588; the thickener is sodium hydroxymethyl cellulose, which can be purchased from Hefei Hongrui Biotechnology Co., Ltd.; the polyolefin diaphragm is made by our company, and the preparation method refers to patent CN202010339196.2, and the polyolefin is polyethylene with a thickness of 9 μm.

[0025] Embodiment 1: A method for preparing a low-moisture lithium battery separator, comprising the following steps:

[0026] S1: Preparation of polystyrene-Al2O3 composite materials:

[0027] Step 1: Add 3.178 g of Al2O3 powder and 250 mL of ultrapure water into a 500 ml three-necked flask, stir magnetically at 650 rpm for 90 minutes, and then treat at 40 KHZ and 400 W ultrasonic power for 8 hours to obtain a uniformly dispersed Al2O3 dispersion;

[0028] Step 2: slowly add 2.26 g of polystyrene into 17.78 g of acetone to obtain a mixed solution, then seal the mixed solution, and then slowly heat it in a water bath to 45° C., and then stir it at 350 rpm for 8 hours using a magnetic stirring device to obtain a polystyrene solution;

[0029] Step 3: Slowly add the polystyrene solution to the uniformly dispersed Al2O3 dispersion through the side port of a three-necked flask at a flow rate of 0.6 ml / min under the conditions of 1000 rpm rotation speed and 40KHZ, 450W ultrasonic treatment; then stir at 400 rpm rotation speed for 2 hours, and then treat at 45KHZ, 450W ultrasonic power for 5 hours to obtain a mixed solution, and then centrifuge the mixed solution at a rotation speed of 8500 rpm for 20 minutes, wash, and vacuum dry at 0.08Mpa vacuum degree and 70°C for 24 hours to obtain a polystyrene-Al2O3 composite material;

[0030] S2: Preparation of polystyrene-Al2O3 composite coating slurry:

[0031] The dispersant and the polystyrene-Al2O3 composite material were premixed in ultrapure water for 70 minutes at a speed of 650 rpm; the thickener was added and stirred for 90 minutes at a speed of 650 rpm; the binder was added and stirred for 90 minutes at a speed of 1000 rpm; the wetting agent was added and stirred for 30 minutes at a speed of 250 rpm; and the polystyrene-Al2O3 composite material coating slurry was obtained after filtering and removing iron;

[0032] The polystyrene-Al2O3 composite material coating slurry comprises the following components, by mass percentage: 0.55% of a dispersant, 15% of a polystyrene-Al2O3 composite material, 0.15% of a thickener, 9% of a binder, 0.7% of a wetting agent, and the balance is ultrapure water;

[0033] S3: Preparation of composite membrane modified by polystyrene-Al2O3 composite material:

[0034] The micro-gravure roller coating process is adopted to evenly roll-coat the prepared polystyrene-Al2O3 composite material coating slurry on both sides of a polyolefin separator with a thickness of 9 μm through a coater. The coating thickness on one side is the same. After baking in an oven at 70°C, the composite separator modified with the polystyrene-Al2O3 composite material for lithium-ion batteries is obtained.

[0035] Embodiment 2: A method for preparing a low-moisture lithium battery separator, comprising the following steps:

[0036] S1: Preparation of polystyrene-Al2O3 composite materials:

[0037] Step 1: Add 3.178 g of Al2O3 powder and 250 mL of ultrapure water into a 500 ml three-necked flask, stir magnetically at 650 rpm for 90 minutes, and then treat at 40 KHZ and 400 W ultrasonic power for 8 hours to obtain a uniformly dispersed Al2O3 dispersion;

[0038] Step 2: slowly add 2.26 g of polystyrene into 17.78 g of acetone to obtain a mixed solution, then seal the mixed solution, and then slowly heat it in a water bath to 45° C., and then stir it at 350 rpm for 8 hours using a magnetic stirring device to obtain a polystyrene solution;

[0039] Step 3: Slowly add the polystyrene solution to the uniformly dispersed Al2O3 dispersion through the side port of a three-necked flask at a flow rate of 0.6 ml / min under the conditions of 1000 rpm rotation speed and 40KHZ, 450W ultrasonic treatment; then stir at 400 rpm rotation speed for 2 hours, and then treat at 45KHZ, 450W ultrasonic power for 5 hours to obtain a mixed solution, and then centrifuge the mixed solution at a rotation speed of 8500 rpm for 20 minutes, wash, and vacuum dry at 0.08Mpa vacuum degree and 70°C for 24 hours to obtain a polystyrene-Al2O3 composite material;

[0040] S2: Preparation of polystyrene-Al2O3 composite coating slurry:

[0041] The dispersant and the polystyrene-Al2O3 composite material were premixed in ultrapure water for 70 minutes at a speed of 650 rpm; the thickener was added and stirred for 90 minutes at a speed of 650 rpm; the binder was added and stirred for 90 minutes at a speed of 1000 rpm; the wetting agent was added and stirred for 30 minutes at a speed of 250 rpm; and the polystyrene-Al2O3 composite material coating slurry was obtained after filtering and removing iron;

[0042] The polystyrene-Al2O3 composite material coating slurry comprises the following components, by mass percentage: 0.55% of a dispersant, 25% of a polystyrene-Al2O3 composite material, 0.15% of a thickener, 9% of a binder, 0.7% of a wetting agent, and the balance is ultrapure water;

[0043] S3: Preparation of composite membrane modified by polystyrene-Al2O3 composite material:

[0044] The micro-gravure roller coating process is adopted to evenly roll-coat the prepared polystyrene-Al2O3 composite material coating slurry on both sides of a polyolefin separator with a thickness of 9 μm through a coater. The coating thickness on one side is the same. After baking in an oven at 70°C, the composite separator modified with the polystyrene-Al2O3 composite material for lithium-ion batteries is obtained.

[0045] Embodiment 3: A method for preparing a low-moisture lithium battery separator, comprising the following steps:

[0046] S1: Preparation of polystyrene-Al2O3 composite materials:

[0047] Step 1: Add 3.178 g of Al2O3 powder and 250 mL of ultrapure water into a 500 ml three-necked flask, stir magnetically at 650 rpm for 90 minutes, and then treat at 40 KHZ and 400 W ultrasonic power for 8 hours to obtain a uniformly dispersed Al2O3 dispersion;

[0048] Step 2: slowly add 2.26 g of polystyrene into 17.78 g of acetone to obtain a mixed solution, then seal the mixed solution, and then slowly heat it in a water bath to 45° C., and then stir it at 350 rpm for 8 hours using a magnetic stirring device to obtain a polystyrene solution;

[0049] Step 3: Slowly add the polystyrene solution to the uniformly dispersed Al2O3 dispersion through the side port of a three-necked flask at a flow rate of 0.6 ml / min under the conditions of 1000 rpm rotation speed and 40KHZ, 450W ultrasonic treatment; then stir at 400 rpm rotation speed for 2 hours, and then treat at 45KHZ, 450W ultrasonic power for 5 hours to obtain a mixed solution, and then centrifuge the mixed solution at a rotation speed of 8500 rpm for 20 minutes, wash, and vacuum dry at 0.08Mpa vacuum degree and 70°C for 24 hours to obtain a polystyrene-Al2O3 composite material;

[0050] S2: Preparation of polystyrene-Al2O3 composite coating slurry:

[0051] The dispersant and the polystyrene-Al2O3 composite material were premixed in ultrapure water for 70 minutes at a speed of 650 rpm; the thickener was added and stirred for 90 minutes at a speed of 650 rpm; the binder was added and stirred for 90 minutes at a speed of 1000 rpm; the wetting agent was added and stirred for 30 minutes at a speed of 250 rpm; and the polystyrene-Al2O3 composite material coating slurry was obtained after filtering and removing iron;

[0052] The polystyrene-Al2O3 composite material coating slurry comprises the following components, by mass percentage: 0.55% of a dispersant, 35% of a polystyrene-Al2O3 composite material, 0.15% of a thickener, 9% of a binder, 0.7% of a wetting agent, and the balance is ultrapure water;

[0053] S3: Preparation of composite membrane modified by polystyrene-Al2O3 composite material:

[0054] The micro-gravure roller coating process is adopted to evenly roll-coat the prepared polystyrene-Al2O3 composite material coating slurry on both sides of a polyolefin separator with a thickness of 9 μm through a coater. The coating thickness on one side is the same. After baking in an oven at 70°C, the composite separator modified with the polystyrene-Al2O3 composite material for lithium-ion batteries is obtained.

[0055] Comparative Example 1: A method for preparing a low-moisture lithium battery separator, comprising the following steps:

[0056] Step 1: Preparation of Al2O3 coating slurry:

[0057] Premix the dispersant and Al2O3 powder in ultrapure water for 70 minutes at a speed of 650 rpm; add the thickener and continue stirring for 90 minutes at a speed of 650 rpm; add the binder and continue stirring for 90 minutes at a speed of 1000 rpm; add the wetting agent and stir for 30 minutes at a speed of 250 rpm; finally filter and remove iron to obtain the Al2O3 coating slurry;

[0058] The Al2O3 coating slurry comprises the following components, by mass percentage: 0.55% dispersant, 15% Al2O3 powder, 0.15% thickener, 9% binder, 0.7% wetting agent, and the balance is ultrapure water;

[0059] Step 2: Preparation of Al2O3 modified composite membrane:

[0060] The Al2O3 coating slurry was evenly coated on both sides of a 9 μm thick polyolefin separator by a micro-gravure roller coating process. The coating thickness on one side was the same. After being baked in an oven at 70°C, the Al2O3-modified composite separator for lithium-ion batteries was obtained.

[0061] Comparative Example 2: A polyolefin separator not coated with slurry was used.

[0062] experiment:

[0063] The composite diaphragms prepared in Examples 1-3 and Comparative Examples 1-2 were used for performance testing, and the moisture content of the coating film was tested using an AKF-CH6 Karl Fischer moisture meter; the air permeability, needle puncture strength, and thermal shrinkage of the battery diaphragm were tested with reference to GB / T36363-2018, and the obtained data are shown in the following table:

[0064]

[0065] Conclusion: The addition amount of the polystyrene-Al2O3 composite material in Example 1 is 15wt%, the addition amount of the polystyrene-Al2O3 composite material in Example 2 is 25wt%, and the addition amount of the polystyrene-Al2O3 composite material in Example 3 is 35wt%. In Comparative Example 1, no polystyrene is used to prepare the polystyrene-Al2O3 composite material, and the polyolefin membrane in Comparative Example 2 is not coated with slurry. From the comparison of the data in the table, it can be seen that with the increase in the addition amount of the polystyrene-Al2O3 composite material, the air permeability value of the membrane is greatly improved. Since polystyrene has strong hydrophobicity and extremely low water absorption, the modification of Al2O3 by polystyrene can significantly improve the problem of high moisture content caused by water absorption of the Al2O3 coated membrane, so that the moisture content of the membrane becomes lower. The present invention adds alumina to the coating slurry. Alumina has good high temperature resistance and thermal conductivity, which is beneficial to improve the heat resistance of the coating, thereby improving the heat resistance of the membrane. Therefore, the longitudinal heat shrinkage of the membranes in Examples 1 to 3 can reach 0.9%, and the transverse heat shrinkage can reach 0.5%, and the heat resistance is excellent. At the same time, the diaphragm also has good mechanical properties and meets the requirements for industrial use. In Comparative Example 1, polystyrene was not used to prepare the polystyrene-Al2O3 composite material. The moisture content of the prepared diaphragm was too high, and the subsequent investment in manpower, material resources and energy consumption increased. In Comparative Example 2, the polyolefin diaphragm was not coated with slurry, and had a low air permeability of only 92s / 100mL. The mechanical properties were poor, and its needle puncture strength was only 380N. The heat resistance was poor, with a longitudinal heat shrinkage of 4.5% and a transverse heat shrinkage of 2.3%. The performance of the diaphragm was poor and did not meet the requirements for industrial use. Therefore, in summary, the composite diaphragm prepared by the present invention has excellent heat resistance, low moisture content and high mechanical strength.

[0066] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium battery separator, characterized in that: The lithium battery separator comprises a base film and a coating layer, wherein the coating layer is arranged on both sides of the base film; the coating layer comprises the following components: a polystyrene-Al2O3 composite material, a dispersant, a thickener, a binder, a wetting agent, and ultrapure water; The preparation method of the polystyrene-Al2O3 composite material is as follows: adding a polystyrene solution to an Al2O3 dispersion, stirring evenly to obtain a mixed solution, centrifuging, washing, and vacuum drying to obtain the polystyrene-Al2O3 composite material; The coating layer comprises the following components, calculated by mass percentage: 0.2%-0.7% of a dispersant, 15%-35% of a polystyrene-Al2O3 composite material, 0.15%-0.85% of a thickener, 1%-11% of a binder, 0.1%-0.7% of a wetting agent, and the balance is ultrapure water.

2. A lithium battery separator according to claim 1, characterized in that: The dispersant is hydrolyzed polymaleic anhydride, the thickener is sodium hydroxymethyl cellulose, the adhesive is COPNA resin, and the wetting agent is a silanol nonionic surfactant.

3. A lithium battery separator according to claim 1, characterized in that: The base film is a polyolefin separator.

4. A method for preparing a lithium battery separator according to claim 1, characterized in that: The method for preparing the battery separator comprises the following steps: Step 1: Take a dispersant and a polystyrene-Al2O3 composite material, add them to ultrapure water, mix them evenly, add a thickener, a binder, and a wetting agent, stir, and filter to obtain a polystyrene-Al2O3 composite material coating slurry; Step 2: Apply the polystyrene-Al2O3 composite material coating slurry on both sides of the polyolefin separator, bake and roll it up to obtain a lithium battery separator.

5. The method for preparing a lithium battery separator according to claim 4, characterized in that: The preparation method of the polystyrene solution is as follows: adding polystyrene into acetone, mixing evenly, heating to 42-45° C., and stirring at a rotation speed of 350-400 rpm for 8-9 hours to obtain the polystyrene solution.

6. The method for preparing a lithium battery separator according to claim 4, characterized in that: The preparation method of the Al2O3 dispersion is as follows: taking Al2O3 powder and ultrapure water, stirring for 90-100 minutes, and then ultrasonically dispersing for 8-9 hours to obtain the Al2O3 dispersion.

7. The method for preparing a lithium battery separator according to claim 4, characterized in that: The polystyrene solution is added to the Al2O3 dispersion, stirred at a speed of 400-500 rpm for 2-3 hours, and then treated at 45KHZ and 450-500w ultrasonic power for 5-6 hours to obtain a mixed solution.

Citation Information

Patent Citations

  • Preparation method of polyolefin diaphragm with high mechanical strength

    CN111525076A

  • Preparation method of alumina-polystyrene hydrophobic coating

    CN109266114A

  • Low-moisture and anti-powder-falling lithium battery diaphragm and preparation method thereof

    CN116646681A